Molecular technologies of mycobacterial research - Shapovalova, Olga; Pozmogova , Svitlana; Zavgorodniy, Andriy (Annals of Mechnikov’s Institute, 2022)
Introduction. Despite significant successes in the fight against human and animal tuberculosis, many aspects of laboratory diagnostics, prevention and treatment of the disease require further improvement. Recently, complex technologies have been successfully implemented that effectively support the advantages of routine and innovative methods of molecular diagnostics and allow solving the urgent problems of detecting extrapulmonary forms of the disease, epidemiology and epizootology of tuberculosis, identifying isolates of non-tuberculous mycobacteria and forms of pathogens resistant to anti-tuberculosis drugs. The purpose of the work is to conduct a comparative analysis of technologies and methodological approaches used in modern laboratories specializing in molecular identification and differentiation of mycobacteria in human and veterinary medicine. We conducted a search for sources of literature covering the problems of diagnostics, treatment and prevention of tuberculosis in the PubMed, Medline, Web of Science, Google Scholar databases from 2001 to 2022. Full-text articles were selected for analysis, including the biological characteristics of mycobacteria, technologies of molecular diagnostic of human and animals tuberculosis and mycobacteriosis, issues of molecular epidemiology of mycobacterial infections, modern methods of detecting resistance of pathogens to antituberculosis drugs. The results of the literature data analysis show that common molecular genetic technologies allow detection MTBC and NTM in culture or specific genetic markers directly in the biomaterial: ITS 16S-23S рРНК, immunodominant antigen HSP65, specific proteins DnaJ, МРТ64, MPB64, IS (IS6110, IS901, IS900, IS1245 and other), genes of resistance to antituberculosis drugs, mutation or deletion of the corresponding genes, etc. Most often, for this purpose, NAAT technologies are used in various modifications, MLPA, MOL-PCR, SNP- typing, DNA probe, PFGE- typing and other. WHO has introduced CB-NAAT, LPA and LAMP cartridge technology for widespread use, on which commercially available test systems from various manufacturers are based. The main molecular technologies used to determine the drug resistance of mycobacteria and the mechanisms of its occurrence are whole-genome sequencing of isolates and analysis of individual genes isolated from clinical samples. Currently, for each antituberculosis drug of the first and second line, as well as for most reserve drugs, genes, specific mutations in which lead to the development of drug resistance, have been identified. For the most studied M. tuberculosis, the list of molecular markers for detection of drug resistance includes a number of constitutive genes encoding the cellular targets of antituberculosis drugs. For this purpose, MLPA technologies with many drug resistance markers (rpoB, katG, inhA, embB) are widely used along with MTBC and NTM genotype detection. Conclusion. Today, molecular technologies are an integral element of almost all diagnostic and epidemiological/epizootological studies of mycobacterial infections. They expand our understanding of the biology of mycobacteria and serve as powerful tools for improving strategies and tactics for the treatment and prevention of diseases caused by these pathogens. The evolution of molecular technologies is in the direction of increasing their sensitivity, specificity, speed, simplicity and reducing the cost of analysis. Molecular technologies known and available today differ in reproducibility, reliability, production cost, degree of standardization, methods of interpreting results, availability of databases for interlaboratory comparative studies conducting. In each specific case, depending on the purpose and object of the study, taking into account the capabilities of the laboratory, the optimal technology for the identification and differentiation of mycobacteria isolated from biomaterial should be selected.